Myoepithelioma of parotid: an unusual clinical entity with immunohistochemistry - Kashyap, Jyoti; Sharma, Ankur; Sharma, Sachin (International Journal of Research in Medical Sciences, 2023)
Myoepithelioma was recognized as a histological distinct entity by World Health organization (WHO) in 1991. Only 1% of all salivary gland neoplasms are myoepithelioma. Most commonly affect parotid in approximately 40%. Myoepithelioma is usually a benign tumour arising from neoplastic myoepithelial cells which lack ductal differentiation. The salivary gland tumors in which the ducts comprise less than 5% of the section are classified as myoepitheliomas and in contrast to pleomorphic adenoma myoepithelioma does not show chondroid or osteoid formation. Immunohistochemical analysis can aid in the diagnosis with immunoreactivity to S-100, P63, Calponin, GFAP and myogenic markers. In this report we present a case of myoepithelioma in retroauricular region.